\(f_t(x)=\frac{1}{t}x^4+x^2-2t\)
Schnitt mit der y-Achse:
\(f_t(0)=-2t\) für alle \(t\)
Schnitt mit der x-Achse:
\(\frac{1}{t}x^4+x^2-2t=0|\cdot t\)
\(x^4+tx^2-2t^2=0|+2t^2\)
\(x^4+tx^2=2t^2\) quadratische Ergänzung:
\(x^4+tx^2+(\frac{t}{2})^2=2t^2+(\frac{t}{2})^2\) 1.Binom:
\((x^2+\frac{t}{2})^2=\frac{9}{4}t^2|±\sqrt{~~}\)
1.)
\(x^2+\frac{t}{2}=\frac{3t}{2}\)
\(x^2=t\) Für \(t>0\):
\(x_1=\sqrt{t}\)
\(x_2=-\sqrt{t}\)
2.)
\(x^2+\frac{t}{2}=-\frac{3t}{2}\)
\(x^2=-2t\) Für \(t<0\):
\(x_3=\sqrt{-2t}\)
\(x_4=-\sqrt{-2t}\)
Extremwerte:
\(f'_t(x)=\frac{4}{t}x^3+2x\)
\(\frac{4}{t}x^3+2x=0\) Satz vom Nullprodukt:
\(x(\frac{4}{t} \cdot x^2+2)=0\)
\(x_1=0\) \(f_t(0)=-2t\) für alle \(t\)
\(\frac{4}{t} \cdot x^2+2=0\)
\(x^2=-\frac{8}{t}\)
\(x_2=\sqrt{-\frac{8}{t}}\) Für \(t<0\)
\(x_3=-\sqrt{-\frac{8}{t}}\) Für \(t<0\)